Relationship of semen characteristics and testosterone profiles with age in growing swamp buffalo bulls (Bubalus bubalis) - Nordin, W.; Bongso, T. A.; Tan, H. S. (1986)
Thirty two swamp buffalo bulls (Bubalus bubalis) ranging in age from 18 months to 72 months with body weights of 300 kg to 470 kg were electroejaculated to study seminal characteristics and age at onset of puberty. First ejaculates could be obtained at 29±3 months at body weights of 380±20 kg with mean values for sperm concentration of 53.9±30.1 x 10 6 cells/ml, motility (50.1±24.1%), live sperm (67.2±15.2%) and total abnormal sperm (10.1±0.9%)at this age. Four bulls younger than 29 months did not give semen on several attempts at electroejaculation. Mean values of semen parameters for ages 30 to 72 months (140 ejaculates from 28 bulls) were : volume 2.5±0.4 ml; general motility 57.9±8.0%; live (unstained) sperm 67.2±1.4% abnormal sperm 11.1±1.8%; sperm concentration 113.0±77.1 x 10 cells/ml and total sperm ejaculate 205.1±51.0 x 10 cells/ml. Volume, motility and sperm concentration increased with age from 29 months to 66 months. Mean (±S.D.) plasma testerone levels for 24 of the same bulls electroejaculated for age groups between 1-2, 2-3, 3-4, 4-5 and >5 years were 82±19, 82±81, 105±55, 63±13 and 90±37 pg/ml respectively, with no apparent trend. When injected with 500ug GnRH or 1000 i.u. H.C.G., peak testosterone levels reached 224±105, 305±293, 377±183, 393±158 and 708±335 pg/ml for the same age groups respectively. Although plasma testosterone was detectable by 1-2 years of age, the results suggest that age - dependent changes (in Ledying cell function) were only evident upon gonadotrophic stimulation, in contrast to half hourly sampling over 6 to 8 hours without GnRH or HCG stimulation. The age at which semen with normal characteristics was first observed (29 months) closely followed the age at which maximum scrotal circumference and maximum seminiferous tubular diameter (32 months) was observed. It thus appears, that while spermatogenesis in completed histologically at 16 months, testosterone secretion is evident as early as 12 months to support spermatogenesis, and ejaculates could be obtained at 29 months. The semen of swamp buffalo bulls could therefore be used for breeding at around 2 1/2 years.